Optimal Pharmaceutical Management Strategies in Cancer Treatment: Novel Approaches - Alishahi, Farhad; Soudmand, Negar; Ghasemi Goki, Tayebeh; Rashidoleslami, Tara Sadat (Asian Pacific Journal of Cancer Nursing, 2025)
Overview: Cancer remains a leading cause of morbidity and mortality, with effective pharmacotherapy essential for improving patient outcomes. This review explores novel strategies in pharmaceutical management, including chemotherapy, targeted therapy, immunotherapy, and personalized approaches, aimed at optimizing cancer treatment and tailoring therapies based on patient profiles. Methods: A literature review was conducted across PubMed, Scopus, and Google Scholar, focusing on studies from the past decade. The review includes clinical trials, meta-analyses, and studies on the mechanisms, effectiveness, and safety of cancer treatments, with a focus on emerging pharmacological approaches, drug resistance, and personalized medicine. Results: Chemotherapy remains the standard treatment, but drug resistance and side effects limit its effectiveness. Novel therapies, such as targeted therapies and immunotherapies, offer more specificity and reduced toxicity. Personalized medicine, based on genetic profiling, is evolving to tailor treatments to individual patients. Despite these advances, challenges like resistance and side effects remain. Conclusion: Pharmacological management of cancer has evolved significantly, with targeted therapies, immunotherapy, and precision medicine offering new treatment options. A personalized, multifaceted approach is crucial for optimizing outcomes. Future research should focus on overcoming resistance and optimizing combination therapies to further improve cancer treatment.